Triclocarban exposure at environmentally relevant concentrations perturbs the gut microbiota and metabolic profile in Rana taihangensis (Anura, Ranidae) tadpoles - Zhao, Ruinan; Liu, Pengyuan; Wu, Yaoyang; Bi, Hongyan; He, Jiaoying; Zhang, Jie; Qu, Yanfu; Chen, Xiaohong; Chen, Zhuo (Frontiers in Microbiology, 2025)
IntroductionThe antibacterial agent triclocarban (TCC) poses a significant threat to aquatic ecosystems and its impact on amphibians remain poorly understood.MethodsHere, we investigated its acute and chronic effects on Rana taihangensis tadpoles at environmentally relevant concentrations (i.e., 5, 15 and 45 μg/L) using an integrated approach combining morphology, gut microbiome, and non-targeted metabolomic analyses.Results and DiscussionThe acute toxicity tests for 96 h revealed that TCC had a lethal concentration (LC50) value of 169.863 μg/L for R. taihangensis tadpoles. Chronic exposure resulted in reduced body condition score across all the three TCC-treated groups compared to the control. Gut microbiome analysis revealed that TCC exposure significantly altered the community composition at both phylum (e.g., Pseudomonadota and Fusobacteriota) and genus (e.g., Cetobacterium and Citrobacter) levels. In addition, several metabolites (e.g., 20-carboxy-leukotriene B4, 11b-PGF2a, and leukotriene E4) associated with immune response and neural signaling were significantly perturbed in TCC-exposed tadpoles. Interestingly, correlation analysis indicated a significant relationship between specific metabolite changes and shifts in gut microbiota. Overall, our findings demonstrated that TCC exposure adversely affects the growth indexes, gut microbial composition and metabolites in R. taihangensis tadpoles, and the present study will provide new insights into the ecotoxicological risks of TCC and enhance the understanding of its mechanisms of toxicity in aquatic organisms.